Aplicação de controle supervisório para a coordenação de esteiras concorrentes em linhas de produção industrial - Dobrovolski, Bruno Manoel (2017)
This work proposes a solution to a problem of coordination of conveyors in an industrial production line, applying Supervisory Control Theory (SCT). The work improves the current method used to determine actions in the production flows, which is essentially manual, and the application takes place into the company Atlas Home appliances. Technically, the work involves the steps of modeling, synthesizing and implementing a controller for multiple conveyors operating in parallel and concurrently. The modeling step maps sensors and actuators, and coordination rules for representation in statemachines. Then, the synthesis step receives this structure of models and obtains a modular set of controllers that are then tested and implemented in C language. For the modularization synthesis step, the techniques of Local Modular Control are used. The implementation explores the use of generic state-machine models, focusing on flexibility, and device and technology independence. In the case study, 4 supervisors were implemented in a single application, with concurrent execution and without an operating system, which adds performance and low consumption of computational resources.